Insight into the molecular mechanism of LINC00152/miR‐215/CDK13 axis in hepatocellular carcinoma progression. Issue 11 (11th July 2019) - Wang, Jianchu; Zhang, Ying; Lu, Libai; Lu, Yuan; Tang, Qianli; Pu, Jian
Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world. Nevertheless, its underlying molecular mechanisms are largely unknown. LINC00152 are recently investigated in several cancer types. In our current investigation, we observed LINC00152 was obviously upregulated in HCC cells. LINC00152 was significantly downregulated by infecting LV‐shLINC00152 in HepG2 and SNU449 cells. Loss of LINC00152 remarkably repressed HCC cell proliferation, cell colony formation, induced cell apoptosis, and restrained cell migration/invasion. Growing evidence has reported long noncoding RNAs can sponge microRNAs to modulate cancer process. Here, we indicated miR‐215 was greatly decreased in HCC and LINC00152 regulated HCC development via sponging miR‐215. For another, the binding association between LINC00152 and miR‐215 was proved by a series of functional assays. CDK13 was predicted as the target of miR‐215. Upregulation of miR‐215 greatly depressed CDK13 in HCC cells. Subsequently, the in vivo results demonstrated that silence of LINC00152 restrained HCC development via modulating miR‐215 to up‐regulate CDK13. Therefore, it was revealed that LINC00152 contributed to the progression of HCC by the modulation of miR‐215 and CDK13. Abstract : We reported LINC00152 was overexpressed in hepatocellular carcinoma (HCC )cells, whereas miR‐215 was inhibited. CDK13 was speculated as the putative target of miR‐215. Herein, we revealed that LINC00152 contributed to the progression of HCC by the modulation of miR‐215 and CDK13.